1986
DOI: 10.1148/radiology.160.2.3726125
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic fractures: value of plain radiography in early assessment and management.

Abstract: Assessment of pelvic fractures in severely traumatized, clinically unstable patients presents a diagnostic problem. Traditional plain-radiographic classifications of the fracture are of limited preoperative value to the surgeon who must apply corrective force in opposition to the original force vector causing the fracture. Computed tomographic scanning is an effective method of examining the pelvis but is time consuming and may be impractical in cases of severe injury. In a retrospective analysis of the plain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
303
1
14

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 542 publications
(320 citation statements)
references
References 0 publications
2
303
1
14
Order By: Relevance
“…Additionally, by recognizing vertical shear injuries, traction can be applied to reduce the proximally displaced hemipelvis. These concepts were articulated by Young et al [27] and continue to be a cornerstone in the evaluation and treatment of patients with pelvic ring injuries.…”
Section: Historymentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, by recognizing vertical shear injuries, traction can be applied to reduce the proximally displaced hemipelvis. These concepts were articulated by Young et al [27] and continue to be a cornerstone in the evaluation and treatment of patients with pelvic ring injuries.…”
Section: Historymentioning
confidence: 99%
“…Tile et al [23] added the concept of stability (ie, stable, vertically stable but rotationally unstable, vertically and rotationally unstable). Acetabular fractures were considered separately in the classifications of Tile et al (comprehensive classification) [23] and Young et al (Young and Burgess classification) [27].…”
Section: Historymentioning
confidence: 99%
See 2 more Smart Citations
“…We prefer to use the Young and Burgess classification system, which classifies injuries by mechanism-vertical shear in the presence of vertical displacement, anterior-posterior compression with significant pubic symphyseal diastasis (APC I, II, III depending on degree of sacroiliac dislocation) or lateral compression fractures (LC I, II, III depending on disruption of contralateral elements and/or iliac wing fracture) [13,14]. There have been several retrospective studies that have shown an association between pelvic fracture classification and risk of arterial injury and/or the need for transfusions [15•, 16].…”
Section: Introductionmentioning
confidence: 99%